Searching for patent foramen ovale in a 44-year-old female patient after ischemic stroke – diagnostic problems - Zalewska-Adamiec, Małgorzata; Kralisz, Paweł; Bachórzewska-Gajewska, Hanna; Dobrzycki, Sławomir (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Patent foramen ovale (PFO) is associated with the occurrence of cryptogenic strokes in young patients. Transesophageal echocardiography with contrast is the established standard in PFO diagnostics. We present the case of a 44-year-old female patient after ischemic stroke, in whom PFO was not detected by echocardiography; the defect was ultimately diagnosed by right heart catheterization.